Antibacterial Activity of Flavonoid-Rich Fractions Of Citrus Maxima Peel Extract - Reh Malem br Karo; Putranto Manalu; Jhon Patar Sinurat (Department of Chemistry - Universitas Bangka Belitung, 2020)
Natural products can be used as an alternative in the treatment of various diseases such as infectious diseases due to the bioactive compounds contained therein. Moreover nowdays, there are many antibiotic resistance in the treatment of infectious diseases. Citrus maxima is one of the natural products. Citrus maxima have been used for many diseases in traditional medicine.The aim of this study was to investigate the antibacterial activity of flavonoid-rich fractions of citrus maxima peel extract. The bioactive compounds contained in Citrus maxima peel were extracted by maceration method using 96% ethanol solvent. Fractionation was conducted using liquid-liquid extraction using a solvent of water and ethyl acetate obtained ethyl acetate fraction. In this fraction, the TLC test was carried out to confirm the presence of phenolic and flavonoid compounds. The antibacterial activity testing for ethyl acetate fraction against S.aureus and E.coli was determined by disk diffusion method with concentration of 25 ppm, 50 ppm, 75 ppm and 100 ppm. The ciprofloxacin and distilled water were used as positive and negative control, respectively. The result of this study showed that ethyl acetate fraction ( flavonoid-rich fractions) Of Citrus Maxima has potential as antibacterial for bacterial S.aureus and E.coli with medium inhibitory ability in all of concentration ranges. The highest inhibition zone for S.aureus was found at a concentration of 100 ppm while for E.coli was at a concentration of 75 ppm.